Design for Advanced Manufacturing : Technologies, and Processes - Gillespie, LaRoux (McGraw-Hill's AccessEngineering., 2017)
Detailed coverage of the latest advances in manufacturing and product design. Edited by a past president of the Society of Manufacturing Engineers, this comprehensive resource features contributions from a host of international manufacturing and design experts. You will get thorough explanations of the entire range of advanced manufacturing processes and technologies as well as practical instructions and technical guidance.